Fertility & Migration Assignment - DeRose, Laurie (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
For this assignment, I want you to focus on three mortality measures: the Crude Death Rate, the Infant Mortality Rate, and Life Expectancy at Birth. There are 3 parts to this assignment: levels, trend, and interpretation (details below). Be sure you do them all.